The Use of Hopscotch Game in Teaching Speaking to the First Grade Students of English Department of IKIP PGRI Madiun in the Academic Year of 2013/2014 - Fitra Pinandhita (Universitas PGRI Madiun, 2013)
Hopscotch Game is one of the media in teaching speaking. It is purposed to help the students more interested in teaching-learning process. The objectives of this research are to describe: 1) the procedure of using hopscotch game in teaching speaking, 2) the advantages of using hopscotch game in teaching speaking, 3) the disadvantage of using hopscotch game in teaching speaking. This research was done at IKIP PGRI Madiun from September-December2013. The subject of the study was the students of 1A of English Department of IKIP PGRI Madiun consisting of 30 students, it uses descriptive qualitative method for data analysis. The researcher did some steps such as pre activity, whilst activity, and post activity. In collecting the data, the researcher applied several techniques including observation, interview, and documentation. The result of the research shows that: 1) there are some procedures of using hopscotch, 2) hopscotch game makes students have fun in speaking class, and it can be a media to motivate students in the teaching-learning process. 3) the disadvantage of hopscotch game is spending much time. Based on the result of this research, some suggestions are presented to the lecturer, and the students. The lecturer is expected to apply various kinds of approach or method such as hopscotch game in teaching speaking in order to make the teaching learning process more interesting and fun. The students are expected to practice speaking English actively without being afraid of making mistakes, because the lecturer will rectify and help them to be better in speaking English.